Pony Pals : Don't Hurt My Pony - Betancourt, Jeanne; Illustrated by Bechem, Paul (New York Scholastic Inc., 1995)
The Pony Pals have to discover who is setting animal traps before someone gets hurt.
Keywords: Ponies -- Trapping -- Horses